1989
DOI: 10.1159/000266769
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Type VI Collagen in the Bovine Cornea

Abstract: Using a specific polyclonal antibody against type VI collagen, the distribution of type VI collagen in the bovine cornea was investigated by indirect immunofluorescence microscopy and immunoelectron microscopy. By immunofluorescence, type VI collagen was detectable throughout the stroma. In addition to the uniform but relatively weak signals, a laminar pattern similar to the arrangement of stromal lamellae was clearly seen. Consistent with the immunofluorescent pattern, immunoelectron micrographs showed strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Subsequently, type VI collagen increased during wound healing and was distributed throughout the wounded area. The electron-microscopic immunolo calization for anti-type VI collagen antibody showed the presence of reaction products in the pericellular region of fibroblastic cells as seen in that of keratocytes in normal bovine corneal stroma [9], In these wounds, therefore, type VI colla gen seems to originate from the fibroblastic cells. Moreover, in the 3-week-old wounds, the immunofluorescence showed a laminar pattern as seen in normal corneal stroma, suggesting the regeneration of the lamellar structure by the fibroblastic cells, although the laminar pattern was irregular and incom plete.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Subsequently, type VI collagen increased during wound healing and was distributed throughout the wounded area. The electron-microscopic immunolo calization for anti-type VI collagen antibody showed the presence of reaction products in the pericellular region of fibroblastic cells as seen in that of keratocytes in normal bovine corneal stroma [9], In these wounds, therefore, type VI colla gen seems to originate from the fibroblastic cells. Moreover, in the 3-week-old wounds, the immunofluorescence showed a laminar pattern as seen in normal corneal stroma, suggesting the regeneration of the lamellar structure by the fibroblastic cells, although the laminar pattern was irregular and incom plete.…”
Section: Discussionmentioning
confidence: 85%
“…A previous immunohistochemical study by Linsenmayer et al [8] using embryonal chicken cornea (secondary stroma) showed that type VI collagen within each lamella was not a component of the striated collagen fibrils, but was assembled in the form of thin filaments. We have reported that type VI collagen is present in the interlamellar space and in the pericellular region of keratocytes [9]. In the present study, the role of type VI collagen in the healing process of full-thick ness trephinized corneal wounds was investi gated by immunohistochemistry.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations